REVIEW PAPERMetalloproteinases in the pathogenesis of systemic inflammatory rheumatic diseases - Olewicz-Gawlik, Anna; Hrycaj, Paweł; Łącki, Jan K. (Reumatologia/Rheumatology, 2005)
Metalloproteinases (MMPs) are a family of enzymes that hydrolyze components of the extracellular matrix. These proteinases play a key role in the majority of biological processes, both physiological, such as embryogenesis, wound healing, angiogenesis, and pathological, like for example rheumatic diseases. The increasing number of evidence concerning the role of metalloproteinases in inflammatory rheumatic diseases shows not only the direction of future researches, but also gives new targets for the therapies of these so far incurable diseases.